Structural insights into the allosteric site of Arabidopsis NADP-malic enzyme 2: role of the second sphere residues in the regulatory signal transmission - Gerrard Wheeler, Mariel Claudia (2021)
t Structure–function studies contribute to deciphering how small modifcations in the primary structure could introduce desirable characteristics into enzymes without afecting its overall functioning. Malic enzymes (ME) are ubiquitous and responsible for a wide variety of functions. The availability of a high number of ME crystal structures from diferent species facilitates comparisons between sequence and structure. Specifcally, the structural determinants necessary for fumarate allosteric regulation of ME has been of particular interest. NADP-ME2 from Arabidopsis thaliana exhibits a distinctive and complex regulation by fumarate, acting as an activator or an inhibitor according to substrate and efector concentrations. However, the 3D structure for this enzyme is not yet reported. In this work, we characterized the NADP-ME2 allosteric site by structural modeling, molecular docking, normal mode analysis and mutagenesis. The regulatory site model and its docking analysis suggested that other C4 acids including malate, NADP-ME2 substrate, could also ft into fumarate’s pocket. Besides, a non-conserved cluster of hydrophobic residues in the second sphere of the allosteric site was identifed. The substitution of one of those residues, L62, by a less fexible residue as tryptophan, resulted in a complete loss of fumarate activation and a reduction of substrate afnities for the active site. In addition, normal mode analysis indicated that conformational changes leading to the activation could originate in the region surrounding L62, extending through the allosteric site till the active site. Finally, the results in this work contribute to the understanding of structural determinants necessary for allosteric regulation providing new insights for enzyme optimization.